Shifting Horizons: A Literature Review of Research Data Management Train-the-trainer Models for Library and Campus-Wide Research Support Staff in Canadian Institutions - Tayler, Felicity; Jafary, Maziar (Université d'Ottawa | University of Ottawa, 2020)
This is a preprint of an article accepted for publication in EBLIP 15.4 (2020). Question: In consideration of emerging national research data management policy and infrastructure, what is the most effective way for a Canadian research university to build capacity of Library and campus-wide research support staff, with a view towards providing coordinated Research Data Management (RDM) support services for our researcher community? What international training models and course offerings are available and appropriate to our local context? What national guidelines and best practices for pedagogical design and delivery can be adapted to a local context? Methods: This literature review synthesizes a total of thirteen sources: nine articles, two book chapters and two whitepapers selected for a narrative literature review due to their focus on case studies detailing train-the-trainer models. Within the thirteen sources, we found fourteen key case studies. The articles reviewed here supplement the 2017 CARL Portage Training Expert Group white paper, “Research Data Management Training Landscape in Canada,” the focus of which was to identify RDM training gaps in order to recommend a coordinated approach to RDM training in a national environment. Results: Three thematic areas emerged from the narrative review of case studies: Pedagogical challenges were identified, including the need to target training to RDM support staff such as librarians and researchers, as they comprise distinct groups of trainees with divergent disciplinary vocabularies and incentives for training. Our case studies cover a broad range of pedagogical models including single or multiple sessions, self-directed or instructor-led, in-person or online instruction, and a hybrid of the two. RDM training also emerged as a key factor in community building within Library staff units, among service units on campus, and with campus research communities. Conclusion: Training programs at local institutions should be guided by a set of principles aligned with the training methods, modes of assessment, and infrastructure development timeline outlined in a national training strategy. When adapting principles and training strategies to a local context, the following trends in the literature should be considered: Librarians (and researchers) must have meaningful incentives to undertake training in RDM or to join a community of practice; disciplinary-specific instruction is preferable over general instruction; a librarian’s own training opportunities will influence their ability to provide discipline-specific RDM instruction to researchers; in-person training opportunities improve learning retention and produce beneficial secondary effects, online instruction is most effective when paired with an in-person component; generalized third-party RDM training should be adapted to local context to be meaningful. Future directions for RDM training will integrate into Open Access and digital scholarship training, and into cross-disciplinary, open science communities of practice.
Keywords: Research Data Management; Training